2022
DOI: 10.1016/j.xhgg.2021.100053
|View full text |Cite
|
Sign up to set email alerts
|

Neural network classifiers for images of genetic conditions with cutaneous manifestations

Abstract: Summary Neural networks have shown strong potential in research and in healthcare. Mainly due to the need for large datasets, these applications have focused on common medical conditions, where more data are typically available. Leveraging publicly available data, we trained a neural network classifier on images of rare genetic conditions with skin findings. We used approximately 100 images per condition to classify 6 different genetic conditions. We analyzed both preprocessed images that were cropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…To provide examples of ways to bolster the standard diagnostic process as well as to build on the impressive findings of previous, related studies, ( Gurovich et al, 2019 ; Duong et al, 2021b ; Hsieh et al, 2021 ; Porras et al, 2021 ), we analyzed and provided a larger dataset of WS and 22q individuals (although these other studies contained a much larger total number of individuals having multiple other diseases). We also compared results for different ages of individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide examples of ways to bolster the standard diagnostic process as well as to build on the impressive findings of previous, related studies, ( Gurovich et al, 2019 ; Duong et al, 2021b ; Hsieh et al, 2021 ; Porras et al, 2021 ), we analyzed and provided a larger dataset of WS and 22q individuals (although these other studies contained a much larger total number of individuals having multiple other diseases). We also compared results for different ages of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…First, we collected a dataset of publicly available WS and 22q images, which may be larger than others previously studied ( Gurovich et al, 2019 ; Liu et al, 2021 ; Porras et al, 2021 ). Second, beyond the dataset, our approaches (and available code) may be used as subcomponents of other algorithms ( Duong et al, 2021b ). We trained a neural network classifier on our dataset (N = 1,894), which is still small compared to many other deep learning datasets, thus pushing the capability of the neural network model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that these types of tools may be effective in many other contexts related to clinical genetics, such as assessing birthmarks, analysing ophthalmologic imaging, and evaluating EEGs or radiologic studies, to name just a few [34 ▪ ,40,41]. In the future, there will be likely tools that can assess more and more data types, including photographic and radiologic images, results of laboratory-based testing, clinical notes and other medical records [42].…”
Section: Reviewmentioning
confidence: 99%
“…AI is not new, but, for a variety of reasons, including better computers, larger, shared datasets, and proven algorithms, AI is garnering increasing attention. The many versions and iterations of AI have already started to be coupled with medical genetics, including in ways that offer glimpses into great potential (a few of many example citations are given) (Brasil et al, 2021; Brasil et al, 2019; Clark et al, 2019; Dias & Torkamani, 2019; Dowsett et al, 2019; Duong et al, 2021; Gurovich et al, 2019; Jumper et al, 2021; Kruszka et al, 2020; Kruszka et al, 2017; Kruszka et al, 2018; Mak et al, 2021; Porras et al, 2021; Schaefer et al, 2020; Shchelochkov et al, 2021; Tekendo‐Ngongang et al, 2020). For example, the use of AI can help develop a differential diagnosis for a patient, can support the analysis of genomic data for that patient, and may help researchers studying possible treatments to select compounds of interest for further study.…”
mentioning
confidence: 99%